Working from Home Around the World - Cevat Giray Aksoy; Jose Maria Barrero; Nicholas Bloom; Steven J. Davis; Mathias Dolls; Pablo Zarate (Institute of Labor Economics (IZA), 2022)
The pandemic triggered a large, lasting shift to work from home (WFH). To study this shift, we survey full-time workers who finished primary school in 27 countries as of mid 2021 and early 2022. Our cross-country comparisons control for age, gender, education, and industry and treat the U.S. mean as the baseline. We find, first, that WFH averages 1.5 days per week in our sample, ranging widely across countries. Second, employers plan an average of 0.7 WFH days per week after the pandemic, but workers want 1.7 days. Third, employees value the option to WFH 2-3 days per week at 5 percent of pay, on average, with higher valuations for women, people with children and those with longer commutes. Fourth, most employees were favorably surprised by their WFH productivity during the pandemic. Fifth, looking across individuals, employer plans for WFH levels after the pandemic rise strongly with WFH productivity surprises during the pandemic. Sixth, looking across countries, planned WFH levels rise with the cumulative stringency of government-mandated lockdowns during the pandemic. We draw on these results to explain the big shift to WFH and to consider some implications for workers, organization, cities, and the pace of innovation.
Keywords: J2; D22; E24; L23; 330; work from home; preferences over working arrangements; commute times; COVID-19; productivity surprises; government lockdown effects; innovation; cities